2008
DOI: 10.1103/physrevlett.101.116808
|View full text |Cite
|
Sign up to set email alerts
|

Surface Electron Accumulation and the Charge Neutrality Level inIn2O3

Abstract: High-resolution x-ray photoemission spectroscopy, infrared reflectivity and Hall effect measurements, combined with surface space-charge calculations, are used to show that electron accumulation occurs at the surface of undoped single-crystalline In2O3. From a combination of measurements performed on undoped and heavily Sn-doped samples, the charge neutrality level is shown to lie approximately 0.4 eV above the conduction band minimum in In2O3, explaining the electron accumulation at the surface of undoped mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
160
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(181 citation statements)
references
References 26 publications
20
160
1
Order By: Relevance
“…Zhang et al [136] employed energy-dependent photoemission, utilizing the inherent variation in surface specificity with photon energy to support this conclusion, providing spectroscopic confirmation of the increased electron density at In 2 O 3 surfaces. Via extrinsic Sn-doping to increase the bulk carrier concentration, it is possible to quench the electron accumulation [134,135]. This provides a mechanism to reconcile these recent results with earlier studies which suggested a depletion of electrons at the surface [131][132][133].…”
Section: Surface Conductivitysupporting
confidence: 62%
See 2 more Smart Citations
“…Zhang et al [136] employed energy-dependent photoemission, utilizing the inherent variation in surface specificity with photon energy to support this conclusion, providing spectroscopic confirmation of the increased electron density at In 2 O 3 surfaces. Via extrinsic Sn-doping to increase the bulk carrier concentration, it is possible to quench the electron accumulation [134,135]. This provides a mechanism to reconcile these recent results with earlier studies which suggested a depletion of electrons at the surface [131][132][133].…”
Section: Surface Conductivitysupporting
confidence: 62%
“…King et al [63,134] have argued that this can be understood within the concept of the charge neutrality level (CNL) [156,157]. Such localised impurities, defects, and surfaces are all examples of broken symmetries -that is, the perfect translational symmetry of the lattice is lost.…”
Section: Overriding Explanation?mentioning
confidence: 99%
See 1 more Smart Citation
“…6 The fundamental band gap is $0.8 eV smaller than the optical band gap of In 2 O 3 , as transitions from states within 0.8 eV of the valence band maximum (VBM) to the conduction band (CB) are symmetry disallowed. 6,7 This understanding helped to rationalize previous XPS band alignments, which had considered that the CBM of In 2 O 3 was 3.75 eV above the VBM. The ability to lower the CBM of In 2 O 3 relative to the vacuum level and also to simultaneously decrease the effective mass of the CBM would have a huge effect on its electronic conductivity and also on the ability to modulate the workfunction and open up the material for other applications, such as hole injection layers in organic photovoltaics.…”
mentioning
confidence: 99%
“…6,24 The position of the valence band edge is influenced by a number of factors including experimental spectral broadening 25 and band bending at the surface, leading for undoped In 2 O 3 to formation of an electron accumulation layer. 7 Despite these complications changes in the position of the valence band edge upon alloying with Tl can be regarded as significant. It is therefore interesting to find that the valence band edge moves to lower binding energy with incorporation of Tl, with an onset at 2.49 eV for a surface x value 0.36. surface region probed by XPS assuming that there is no change in the band bending.…”
mentioning
confidence: 99%